Predictive factors of mortality due to atherosclerotic heart disease in elderly - Naifi Hierrezuelo Rojas; German del Rio Caballero; Alfredo Hernández Magdariaga; Rolando Bonal Ruiz (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Cardiovascular diseases constitute the first death cause in Cuba and the world. Objective: To identify the predictive factors of deaths due to atherosclerotic cardiovascular disease in elderly people. Methods: An analytic case-control type study was carried out that included 237 dead patients due to atherosclerotic heart disease (cases) and 711 living elderly (control), belonging to 3 health areas of Santiago de Cuba municipality, from January to December, 2021. Results: The predictive factors that were part of the model were nicotine addiction, not very healthy diet, physical inactivity, diabetes mellitus, chronic renal disease, fragility, cognitive deterioration and multimorbidity. Conclusions: The traditional risk factors selected in this study, combined with other potential conditions, improved the prediction of mortality due to heart disease in elderly and facilitated the orientation of preventive interventions in this population group.